Pelanggaran Prinsip Etika Audit dalam Dysfunctional Audit Behavior: Violation of Audit Ethics Principles in Dysfunctional Audit Behavior - Djamil, Nasrullah (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2023)
Dysfunctional Audit Behavior (DAB) poses a significant threat to the integrity of audit practices and ethical standards. This research delves into the intricate web of ethical violations within DAB, examining the deviations from established ethical principles in the field of auditing. The study employs a comprehensive qualitative research methodology, incorporating interviews, case analyses, and ethical frameworks to unravel the underlying factors contributing to these violations. The research uncovers the multifaceted nature of ethical breaches within DAB, focusing on issues related to impartiality, integrity, objectivity, professionalism, and confidentiality. Through in-depth analyses of real-world cases and interviews with auditors, clients, and regulatory bodies, this study aims to identify patterns and motivations driving auditors towards unethical practices. Moreover, the research explores the impact of these violations on the credibility of audit reports and the overall trust in the auditing profession. The findings of this research not only shed light on the root causes of ethical misconduct but also offer valuable insights for regulatory bodies, audit firms, and educators. By understanding the complexities of DAB, stakeholders can develop targeted strategies to prevent and mitigate these violations effectively. Strengthening ethical education, enhancing regulatory oversight, and fostering a culture of integrity within audit organizations emerge as key recommendations from this study.